“Presidential Sistem of the USA through a prism of the Roman Republic” - Runcheva Tasev, Hristina; Apostolovska-Stepanovska Milena (Macedonian Political Science Forum, 2016)
The United States is an original and best-known model of a presidential system in the world. Its originality is incontestable, but its roots may be found in the history of the Roman Republic as a universal and timeless model of organization of government. The authors argue that there is a strong impact of the legacy of the Roman Republic on the modern concept of presidential system in the United States by drawing many similarities and parallels between them. Therefore, this paper analyses whether Polybius and his works influenced the “founding fathers” of modern America, and whether the US Constitution is based on ancient theories of the Roman Republic.